TikTok Creators' Strategies for Delivering Islamic Character Education to Generation Z - Haya Haya; Bahtyar Hardyansyah Syihab (Indonesian Journal of Progressive Pedagogy, 2025)
This study explores TikTok creators’ strategies for delivering Islamic character education to Generation Z. Using a qualitative descriptive–exploratory approach, data were collected through observation, semi-structured interviews, and documentation, then analyzed by interactive model using  NVivo 12 software. The findings reveal three major strategies: first, the careful selection of Islamic content themes, emphasizing values such as honesty, respect, and responsibility contextualized through humor and storytelling; second, the interactive use of TikTok features, including live streaming, duets, and comment engagement, which foster participatory learning; and third, negotiation with algorithmic challenges, requiring creators to adapt Islamic messages within entertaining formats to ensure visibility. The study concludes that TikTok can serve as an effective medium for Islamic education when creators adaptively balance educational depth with cultural and technological dynamics. This research contributes theoretically to digital Islamic pedagogy and practically to educators, policymakers, and da’wah practitioners seeking to engage Generation Z effectively.